Comparative study of secondary mathematics curriculum between Malaysia and Singapore - Ibrahim, Zarina Bibi; Othman, Khairil Iskandar (Elsevier, 2010)
This preliminary study attempts to compare the Malaysian Secondary Mathematics (MSM) curriculum published in 2003 with the Singapore Secondary Mathematics (SSM) implemented in 2007. The study aims to examine the math content and the level at which the content is introduced between the two countries. The results from the study indicated that there is a need for Malaysia Mathematics Curriculum to be revised in order to enable students to have literacy in mathematics and the ability to apply mathematics into other disciplines at higher level.